2013
DOI: 10.1371/journal.pone.0073354
|View full text |Cite
|
Sign up to set email alerts
|

Superior Cross-Species Reference Genes: A Blueberry Case Study

Abstract: The advent of affordable Next Generation Sequencing technologies has had major impact on studies of many crop species, where access to genomic technologies and genome-scale data sets has been extremely limited until now. The recent development of genomic resources in blueberry will enable the application of high throughput gene expression approaches that should relatively quickly increase our understanding of blueberry physiology. These studies, however, require a highly accurate and robust workflow and make n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Therefore, one has to resort also to the homology-based selection of candidate genes. The identification of suitable candidates can be strongly improved by using orthologs of genes that were experimentally verified as appropriate references in related organisms under similar experimental or developmental conditions [ 38 , 74 76 ]. We used such an approach to identify the pepper orthologs of our new superior tomato reference genes and determined UCH and PHD as the most suitable references for normalization of plant gene expression in the Xcv -pepper pathosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one has to resort also to the homology-based selection of candidate genes. The identification of suitable candidates can be strongly improved by using orthologs of genes that were experimentally verified as appropriate references in related organisms under similar experimental or developmental conditions [ 38 , 74 76 ]. We used such an approach to identify the pepper orthologs of our new superior tomato reference genes and determined UCH and PHD as the most suitable references for normalization of plant gene expression in the Xcv -pepper pathosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In plant science, growing efforts have been made in recent years. Stable reference genes have been identified in variety of plants, such as Arabidopsis ( Lilly et al, 2011 ), grasses ( Hong et al, 2008 ; Lee et al, 2010 ), fruits ( Clancy et al, 2013 ; Die and Rowland, 2013 ; Imai et al, 2014 ), vegetables ( Wan et al, 2010 ; Xu et al, 2012 ), commercial agricultural crops ( Figueiredo et al, 2013 ; Wang et al, 2013b ), and some desert plants ( Li et al, 2012 ; Shi et al, 2012 ; Zhu et al, 2013 ). The development of next generation sequencing technology provides new opportunities to explore the genetic resources from an expanding selection of plants ( Czechowski et al, 2005 ; Hong et al, 2010 ; Narsai et al, 2010 ; Demidenko et al, 2011 ; Feng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been introduced to normalize the expression of reference genes, including software such as geNorm (Vandesompele et al, 2002), NormFinder (Andersen et al, 2004), qBase plus (Hellemans et al, 2007), and BestKeeper (Pfaffl, 2001). Among the studies in which geNorm, NormFinder, and qBase plus have been simultaneously used for normalization, some minor differences have been shown among these three programs in terms of evaluating the best sets of reference genes in blueberry (Die and Rowland, 2013), oil palm (Yeap et al, 2014), and citrus (Yan et al, 2012). Moreover, studies in longan [Dimocarpus longan (Lin and Lai, 2010)], tobacco (Schmidt and Delaney, 2010), and rubber tree [Hevea brasiliensis (Li et al, 2011)] have reported substantial differences between geNorm and NormFinder.…”
Section: Performance Of the Primers For Each Reference Genementioning
confidence: 99%
“…Therefore, it is vital to select ideal reference genes to normalize RT-qPCR analysis. Recently, research into evaluating the stability of potential reference genes across various experimental conditions has been performed in different plant species such as chamomile [Chrysanthemum lavandulifolium (Fu et al, 2013)], cineraria [Senecio cruentus (Jin et al, 2013)], blueberry [Vaccinium vitis (Die and Rowland, 2013)], oil palm [Elaeis quineensis (Yeap et al, 2014)], chinese iris [Iris lactea var. chinensis (Gu et al, 2014)], and mei flower [Prunus mume (Wang et al, 2014)].…”
mentioning
confidence: 99%